Small extracellular vesicles derived from in vivo‐ or in vitro‐produced bovine blastocysts have different miRNAs profiles—Implications for embryo‐maternal recognition. Issue 9 (16th August 2021) - Bridi, Alessandra; Andrade, Gabriella M.; del Collado, Maite; Sangalli, Juliano R.; de Ávila, Ana C. F. C. M.; Motta, Igor G.; da Silva, Júlio C. B.; Pugliesi, Guilherme; Silva, Luciano A.; Meirelles, Flávio V.; da Silveira, Juliano C.; Perecin, Felipe
Abstract: In vivo‐ and in vitro‐produced bovine embryos have different metabolic profiles and differences in gene transcription patterns. These embryos also have a distinct ability to establish and sustain early pregnancies. Small extracellular vesicles (sEVs) are secreted by embryos and carry bioactive molecules, such as miRNAs. We hypothesize that in vivo or in vitro‐produced bovine hatched blastocysts on Day 9 and the sEVs secreted by them have different miRNA profiles. To address this hypothesis, embryos of both groups were placed in in vitro culture on Day 7. After 48 h, hatched embryos and hatched embryo‐conditioned media (eCM) of both groups were collected. A total of 210 miRNAs were detected in embryos of both groups, of these 6 miRNAs were downregulated, while 7 miRNAs were upregulated in vitro group when compared to in vivo group. sEVs were isolated from eCM to determine miRNA profile. A total of 106 miRNAs were detected in both groups, including 14 miRNAs upregulated in sEVs from in vivo‐eCM, and 2 miRNAs upregulated in sEVs from in vitro‐eCM. These miRNAs express in embryos and sEVs secreted by them regulate early embryonic developmental and endometrial pathways, which can modify embryo‐maternal communication during early pregnancy and consequently affect pregnancy establishment.